Expectations, needs and opportunities of pre-service teachers in view of science teaching in primary education - Ángel Luis Cortés Gracia; Milagros de la Gándara Gómez; José Miguel Calvo Hernández; María Begoña Martínez Peña; Julia Ibarra Murillo; Javier Arlegui de Pablos; María José Gil Quílez (Enseñanza de las Ciencias, 2012)
This paper presents the results of the analysis of several surveys conducted in three key moments in the training of teachers regarding science education. Before starting the courses, training expectations are heavily influenced by the vision of the chosen specialty. Among the real needs they include the theoretical contents of science, although many students reported their preferences for learning about teaching strategies. Upon completion of the courses, training teachers point out the importance of many more aspects than originally planned, leaving aside the theoretical aspects of science. Finally, after the practicum, many pre-service teachers say that all this has little application in the classroom and show the limited opportunities to implement what they learned in university.